Exploring the Virtual-Representational-Abstract Instructional Sequence Across the Learning Stages for Struggling Students. Issue 3 (May 2023) - Bouck, Emily; Long, Holly; Bae, Yukyung
In recent years, virtual manipulatives have been explored and used as an alternative to concrete manipulatives in mathematics for students on their own and as part of manipulative-based instructional sequences. Researchers examining virtual manipulative-based instructional sequences tend to focus on students documented with disabilities, as opposed to students at-risk or struggling with mathematics, as well as students' acquisition of the target skill, despite students experiencing learning in four stages: acquisition, fluency, maintenance, and generalization. This study explored the virtual-representational-abstract (VRA) instructional sequence across four stages of learning for three elementary students struggling in mathematics. In the single-case design study, researchers found a functional relationship between the VRA instructional sequence delivered online via explicit instruction and students' computational accuracy in their targeted area of mathematics need. Researchers also found limited influence on fluency rate or generalization to word problem accuracy but that students did maintain.